Gender Equality Plan Development in Universities: A Strategic Management Perspective (European journal of volunteering and community-based projects, 2024)
Gender equality and the empowerment of women of all ages are universal goals. Achieving gender equality necessitates actions that cut across many policy sectors, from education, social protection and the labour market to property rights, fiscal systems, infrastructure and governance. Gender equality plans (GEPs) are a component of European policies aimed at improving gender equality in higher education organizations such as universities. This study focuses on the GEP development process through the use of action research. An Italian University is deemed as a suitable case study. The approach adopted in the study is the interventionist one. To this purpose, the authors were directly involved in the process of defining the GEP of the University of Messina, by engaging, training and coordinating the organization’s stakeholders and by drafting the GEP document. This work contributes to both literature and practice. First, it provides a GEP development approach based on strategic planning and management theory that might be applied to other organizations and governmental sectors. Moreover, by describing the University’s GEP development process, it also contributes to the literature and propagates analytical techniques connected to gender mainstreaming in Italian institutions.